Efeito antinociceptivo do monoterpeno (S)-(-)-álcool perílico em camudongos - Benedito, Rubens Batista (2009)
Essential oils are natural products with different applications, especially in the area therapeutic and cosmetic. Many essential oils exhibit a variety of pharmacological properties level of CNS, such as anxiolytic, anticonvulsant and antinociceptive. The influence of functional groups in the structures of these molecules in relation to psychopharmacological effect has also been investigated. These effects are probably due to great structural diversity of the essential oils constituents. The (-)-menthol is a monoterpene that belongs to the series of p-menthane terpenes, and has central antinociceptive activity involving the opioid system. Perillyl alcohol (p-Mentha-1, 8-diene-7-ol) is also a member of the family of monoterpenes, with structure similar to menthol, being found in plants of the genus Lavandula, Mentha, Cymbopogon, among other, whose antinociceptive activity had not already been studied. Based on this chemical and structural similarity, this study investigated the antinociceptive activity of (S)-(-)-perillyl alcohol (PA) in animal models. The study began with the screening behavioral pharmacology and the determination of the LD50, concomitantly. The screening, results indicated a depressant activity in the CNS and the LD50 doses were chosen for subsequent tests (50, 75, 100 mg / kg). In order to investigate a possible miorelaxant and neurotoxic activity that could interfere with the results, the rota-rod test was conducted, where there was no such effect. Next, methods to evaluate the antinociceptive activity were used. The first was the writhing induced by acetic acid, then the formalin test and finally the hot plate, which is specific for central antinociceptive activity. In the three methods used, PA was show be significantly effective. Therefore, from these experimental data, we can infer that the PA has central antinociceptive activity , but mechanisms involved remain unknown.